Nora Fardella Olivares: A Biography [Nora Fardella Olivares: Uma História Biográfica] [Nora Fardella Olivares: Un Relato Biográfico] - Castillo-Lobos, L; Nunez-Carrasco, E (Universidad de Concepcion, 2022)
Objective: To strengthen the historical foundations of Chilean nursing, represented in the figure of the nurse Nora Fardella Olivares, by making visible her contributions to national nursing, analyzed from a professional identity approach. Material and Method: Based on the qualitative paradigm and biographical method, the findings were obtained from primary and secondary documentary sources and from the accounts of four key informants, selected by means of intentional theoretical sampling, who have had the opportunity to meet and work with Nora Fardella. The findings obtained were analyzed thematically around the professional nursing identity represented by Nora Fardella during her work as an outstanding health nurse, academic and nurse’s rights advocate. Results: There are several findings that highlight Nora Fardella’s work and experience. From her professional beginnings and as a result of her intellectual restlessness, she managed to expand the scope of her work towards political and intellectual spaces where she was able to scientifically communicate the results of her work, in addition to advocating for the needs of the community and the nursing workers from a critical and ethical position. Conclusion: The versatility of her professional career, the broad scope of her intellectual production, marked by her ethical and value-based approach, contribute to making Nora Fardella an icon of Chilean nursing and a key figure for national health care in the 20th century. © 2022, Universidad de Concepcion. All rights reserved.